Seismic source of 2007 Pisco earthquake obtained from tidal waveform inversion - Jiménez, César (2012)
An earthquake shooked the central-southern zone of Peru, on august 15, 2007. As coseismic effect a tsunami was generated, which flooded some villages and beach resorts. From analysis and signal processing of nine tidal records observed, we can get the parameters characterizing the initial coseismic deformation through an inversion process, in which the computed signal is compared with the observed signal by a non-negative least square process. The maximum slip is 7.0 m and is located on the southern part of rupture geometry. The calculated scalar seismic moment is M0 = 1.99 × 10<21> Nm, equivalent to a magnitude of 8.1 Mw. As a result, a heterogeneous seismic source model is obtained, which was the initial condition for simulating tsunami propagation and inundation.